v.3 c.1 - Parthasarathy, R. (ed.); Dholakia, Ravindra H. (ed.) (New Delhi, 2011)
This three-book volume series aim to describe and document the processes of evolution and the contribution of the Sardar Sarovar Project (SSP) on Narmada River in Gujarat. The SSP has a long and interesting history witnessing multifaceted issues over the last 65 years; The last decade of which has resolution of many of the matters relating to construction of the dam. Pioneer engineers, scholars, activists and policy makers, most of whom had firsthand knowledge of issues involved in the SSP have contributed chapters under three themes the History of Design, Planning and Appraisal including the Environment, the Resettlement and Rehabilitation process during implementation and the Impacts So Far and Ways Forward.
Keywords: Sardar Sarovar Project